The Effect and Mechanism of Cholesterol and Vitamin B12 on Multi-Domain Cognitive Function: A Prospective Study on Chinese Middle-Aged and Older Adults - Wang, Lijing; Liu, Kuo; Zhang, Xiaona; Wang, Yushan; Liu, Wen; Wang, Tao; Hao, Ling; Ju, Mengwei; Xiao, Rong (Frontiers in Aging Neuroscience, 2021)
Background: Nutrients are associated with cognitive function, but limited research studies have systematically evaluated on multi-domain cognitive function. The aim of this study was to investigate the effect and mechanism of specific nutrient on multi-domain cognitive function, and provide nutrition guidance for improving cognitive function. Methods: Participants were selected based on a multicenter prospective study on middle-aged and older adults in China. Global cognitive function was evaluated by the Mini-Mental State Examination (MMSE). Nutrients intake was assessed according to food frequency questionnaire and China Food Composition Database, and principal component analysis was performed to extract nutrient patterns. Associations between specific nutrients and cognitive function were assessed using log-binomial regression. Restricted cubic spline was used to illustrate the dose-response relationship of nutrients with multi-domain cognitive function. Mediation analysis was used to determine the mechanism of nutrients in cognitive function. Results: Four nutrient patterns were identified (vitamin-mineral, protein-carbohydrate, fatty acid-vitamin E, and cholesterol-vitamin B12), and only a nutrient pattern rich in cholesterol and vitamin B12 was found associated with cognitive function (RR = 0.891, 95%CI = 0.794–0.999). In multi-domain cognitive function, dietary cholesterol and vitamin B12 were related to better performance of visual memory function (P = 0.034, P = 0.02). In dose-response relationship, it suggested a U-shaped association between vitamin B12 and MMSE (P = 0.02) within a certain range. Conclusions: Dietary intake rich in cholesterol and vitamin B12 was associated with better cognitive function, and vitamin B12 had a U-shaped dose-response relation with MMSE. Thus, ensuring moderate cholesterol and vitamin B12intake may be an advisable strategy to improve cognitive function in middle-aged and older adults. Clinical Trial Registration: EMCOA, ChiCTR-OOC-17011882, Registered 5th, July 2017-Retrospectively registered, http://www.medresman.org/uc/project/projectedit.aspx?proj=2610